Body typing of children and adolescents using 3D-body scanning. - Loeffler-Wirth, H.; Vogel, M.; Kirsten, T.; Glock, F.; Poulain, T.; Korner, A.; Loeffler, M.; Kiess, W.; Binder, H. (PLoS One, 2017)
Three-dimensional (3D-) body scanning of children and adolescents allows the detailed study of physiological development in terms of anthropometrical alterations which potentially provide early onset markers for obesity. Here, we present a systematic analysis of body scanning data of 2,700 urban children and adolescents in the age range between 5 and 18 years with the special aim to stratify the participants into distinct body shape types and to describe their change upon development. In a first step, we extracted a set of eight representative meta-measures from the data. Each of them collects a related group of anthropometrical features and changes specifically upon aging. In a second step we defined seven body types by clustering the meta-measures of all participants. These body types describe the body shapes in terms of three weight (lower, normal and overweight) and three age (young, medium and older) categories. For younger children (age of 5-10 years) we found a common 'early childhood body shape' which splits into three weight-dependent types for older children, with one or two years delay for boys. Our study shows that the concept of body types provides a reliable option for the anthropometric characterization of developing and aging populations.
Keywords: Adolescent; *Anthropometry; Child; Child, Preschool; Humans; *Imaging, Three-Dimensional; Urban Population